Socio-economic Impacts of Community-based Rehabilitation of Degraded Lands: Evidence from North Showa Zone, Oromia-Ethiopia - Ferede, Alemtsehaye; Ayana, Alemayehu (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
A large part of research to date is devoted to the rehabilitation of degraded landscapes focused on technical aspects. This paper evaluated the socio-economic outcomes of Community-Based Rehabilitation of Degraded Land (CBRDL) in the North Showa area of Oromia Regional State, Ethiopia. Multistage sampling techniques were used. In the first stage, the research site is selected based on years of experience in community-based rehabilitation of degraded lands (CBRDL), then simple random sampling techniques were used to select households from two target populations. Data were analyzed using the Statistical Package for Social Science. The findings revealed that the CBRDL brought about reductions in soil erosion and flooding and increased water availability, increased vegetation cover, and crop productivity. Although a people-centered planning approach was promoted during the intervention, a top-down approach prevailed and much needs to be done to overcome the persistent top-down planning process. Lack of knowledge, low level of awareness, low income, and small household size were identified as the main factors affecting participation in the rehabilitation of degraded lands. The overall evaluation showed that the CBRDL is showing encouraging positive impacts.